2015
DOI: 10.3382/ps/pev045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of DL-selenomethionine vs sodium selenite and seleno-yeast on antioxidant activity and selenium status in laying hens

Abstract: The aim of this study was to compare the effect of DL-selenomethionine (SM) with 2 routinely used Se sources, sodium selenite (SS) and seleno-yeast (SY), on relative bioavailability based on antioxidant activity and tissue Se content. Six hundred thirty 131-day-old brown laying hens were randomly assigned to 7 treatments for 168 d (24 wks) with 6 replicates of 15 hens per replicate. The SS and SY animals were supplemented a cornmeal and soybean diet that supplied a total Se 0.3 mg/kg whereas SM was added at 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 55 publications
6
39
2
Order By: Relevance
“…These findings obviously contrast with the findings of other authors (Surai 2000a, b;Paton et al 2002;Mohiti-Asli et al 2008;Gajcevic et al 2009;Scheideler et al 2010;Jing et al 2015) who reported that the majority of organic Se compounds (in ng/g of wet matter) were deposited in the yolk rather than the albumen. However, if these data are corrected for dry matter with estimates of approximately 500 g/kg for the yolk and 200 g/kg for the albumen (Solomon 1991), the concentration of selenium in the albumen is greater than or equal to that in the yolk (Pappas et al 2005).…”
Section: Selenium Content In Eggs After Supplementationcontrasting
confidence: 98%
See 1 more Smart Citation
“…These findings obviously contrast with the findings of other authors (Surai 2000a, b;Paton et al 2002;Mohiti-Asli et al 2008;Gajcevic et al 2009;Scheideler et al 2010;Jing et al 2015) who reported that the majority of organic Se compounds (in ng/g of wet matter) were deposited in the yolk rather than the albumen. However, if these data are corrected for dry matter with estimates of approximately 500 g/kg for the yolk and 200 g/kg for the albumen (Solomon 1991), the concentration of selenium in the albumen is greater than or equal to that in the yolk (Pappas et al 2005).…”
Section: Selenium Content In Eggs After Supplementationcontrasting
confidence: 98%
“…According to several studies, dietary supplementation with selenium increases its abundance in eggs (Surai 2000b;Stibilj et al 2004;Benkova et al 2005;Skřivan et al 2006;Pan et al 2007;Mohiti-Asli et al 2008;Chinrasri et al 2009;Jing et al 2015).…”
Section: Selenium Content In Eggs After Supplementationmentioning
confidence: 99%
“…Significantly more respondents recommended an organic compound, such as selenomethionine, as compared to an inorganic compound, such as sodium selenite. In an animal model of laying hens, a higher antioxidant activity has been demonstrated for the organic versus the inorganic form [40], while in humans both the inorganic Se compounds and the organic derivatives gave rise to steady-state levels of GPx activity after 1 month of supplementation. However, the Se levels in the subjects receiving organic Se showed a steady rise during the whole period, whereas those supplemented with inorganic Se levelled off after a period of 1–3 months [41].…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that SOD in adult birds is also affected by Se status. For example, laying hens fed the Se-supplemented diet showed higher SOD and GSH-Px activity and lower MDA content in plasma compared with those fed the control (non-supplemented) diet [101]. Positive effects of dietary Se on SOD activities in avian species depend not only on Se concentration, but also on the form of Se used, with organic Se being more effective than sodium selenite.…”
Section: Seleniummentioning
confidence: 99%